(untitled) (Global Journal of Medical Research, 2025)
Aims and Objectives The effectiveness of medicinal plants in treating a wide range of illnesses is well known frequently outperforming that of allopathic medicine The purpose of this review is to clarify these plants and their chemical components anti-fertility characteristics It gathers current research on medicinal plants with anti-fertility properties that have been verified by science Methodology An extensive bibliographic analysis was conducted encompassing classical textbooks peer-reviewed articles and reputable global scientific databases Searches were performed in Central Embase Niscair Scopus Google Scholar and PubMed using keywords related to the antifertility activity of plants